Integrated Approaches for Making Settlements Resilient from Earthquake Vulnerability: A Case Study of Urban and Rural Setting in Jajarkot, Karnali Province, Nepal - Singh, Ramesh Prasad; Praveen, B. M. (International Research Journal of MMC, 2025)
This paper explores the integration of indigenous and engineering approaches to reduce earthquake vulnerability in both urban and rural settings of Jajarkot District, Nepal—specifically focusing on Bheri Municipality (Khalanga Bazar) and Barekot Rural Municipality, the latter being the epicenter of the 6.4 magnitude earthquake on November 3, 2023. The earthquake caused significant damage in Jajarkot and Rukum districts, underscoring the urgency of risk reduction. The study highlights that ongoing changes, such as modernization and population growth, have increased the vulnerability of settlements. Four key issues contributing to this vulnerability include poor living environments, weak governance, increasing social segregation, and the erosion of traditional materials and knowledge. The research emphasizes that both urban and rural areas require tailored mitigation strategies that blend technical solutions with local knowledge. Engineering and non-engineering studies underline the complexity of addressing both existing and future built environments. In both settings, communities possess valuable skills, traditional construction knowledge, and mutual support systems that, if harnessed effectively, can enhance resilience. The study concludes that relying solely on either engineering or indigenous methods is insufficient in the face of rapid urbanization and limited local resources. A hybrid approach that leverages traditional building forms, local materials, and collective practices alongside modern engineering techniques is essential for effective and sustainable earthquake risk mitigation.